Vitamin D as a Neuroactive Substance: Review - Stephen J. Kiraly; Michael A. Kiraly; Rick D. Hawe; Naila Makhani (The Scientific World Journal)
The objectives of this paper were (1) to review recent research on the actions of vitamin D as a steroid derivative with neuroactive properties and (2) to highlight clinical relevance and need for more research. Our methods included review of research from current journals, Medline, and Cochrane Reviews; theoretical discussion. Scientific research has had a justifiably strong emphasis on how vitamin D affects calcium metabolism and bone. This appears to have eclipsed its fundamental actions on several other important systems, including the central nervous system. Vitamin D as a neuroactive compound, a prohormone, is highly active in regulating cell differentiation, proliferation, and peroxidation in a variety of structures, including the brain. Vitamin D insufficiency is not rare. Historically, focus has been on bone metabolism, which appears to have caused research bias and evidence bias, distorting physiological importance. The central nervous system is increasingly recognized as a target organ for vitamin D via its wide-ranging hormonal effects, including the induction of proteins such as nerve growth factor. We need more research on this important neuroactive substance because it may play a role as a relatively safe and inexpensive pharmaceutical in the prevention and treatment of a number of common neuropsychiatric conditions.